Storymaking and Drama. An Approach to Teaching Language and Literature at the Secondary and Postsecondary Levels - King, Nancy (Portsmouth Heinemann, 1993)
In Story and Drama teachers will find thoughtful, practical, inventive, and creative ways to explore literature and drama in the classroom. The book is designed to support teachers as they seek ways to find their own approaches to teaching and learning. The author has included many stories from around the world to make the book a joy to read and help to stimulate the development of new ideas for classroom educational practice.
Keywords: Teaching English